MEMBANGUN BUDAYA MEMBACA PADA ANAK USIA DINI DI ERA DIGITAL - Uswatun Hasanah; Much Deiniatur (Universitas Muhammadiyah Metro, 2019)
In this modern era, the interest in reading in children is very alarming. Nowadays children prefer to play gadgets or games rather than reading, even though reading is a window to the world. By reading we can add insights and knowledge that we have never known before. Children prefer to play games or social media rather than looking engrossed in spending time reading books.Keywords: reading, early childhood, digital age